Analisis Pelayanan Transjabodetabek Rute Poris Plawad-Bundaran Senayan Sebagai Moda Transportasi Angkutan Massal Penduduk Pinggiran ke Pusat Kota - Septiawati, Finda; Basuki, Yudi (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2017)
Jakarta is a city with a high economic growth rate and continues to increase. Moreover, Jakarta's economic growth led to the development in the surrounding area, especially in Tangerang which had the settlement functions. To serve the mobility of Tangerang's inhabitants to Jakarta, Central Government developed a Bus Rapid Transit (BRT) system as the implementation of a mass transportation in the exclusive bus lane (Busway). One of the BRT routes is Transjabodetabek Poris Plawad-Bundaran Senayan that serve mobility from Tangerang City to City Center of Jakarta (Bundaran Senayan Zones). The service standards analyzed by a comparative method which compares the patterns from field observation findings to the service standards. The quality of service analyzed with the quantitative descriptive method. Based on the findings, 45% of respondents chose for the reason of efficiency associated with more cheap fares. However, the result of the assessment against the standards, the level of service only reached weight values of 16 from 30 total weight rating. It means that there are several factors that still unwell and need to be improved. Furthermore, from the passenger perceptions, the service quality of Transjabodetabek categorized as quite satisfied. The addition of the fleet which should operate as many as 15 buses being only 10 buses per day. It is necessary to improve the quality of service of this Transjabodetabek routes to realize better sustainable transportation system.